The life of Louis XVI - Hardman, John, 1944- (Yale University Press, 2016)
Louis XVI of France, who was guillotined in 1793 during the Revolution and Reign of Terror, is commonly portrayed in fiction and film either as a weak and stupid despot in thrall to his beautiful, shallow wife, Marie Antoinette, or as a cruel and treasonous tyrant. Historian John Hardman disputes both these versions in a fascinating new biography of the ill-fated monarch. Based in part on new scholarship that has emerged over the past two decades, Hardman's illuminating study describes a highly educated ruler who, though indecisive, possessed sharp political insight and a talent for foreign policy; who often saw the dangers ahead but could not or would not prevent them; and whose great misfortune was to be caught in the violent center of a major turning point in history.
Keywords: Louis -- XVI, -- King of France, -- 1754-1793.; Louis -- XVI, -- King of France, -- 1754-1793; Ludwig -- XVI. -- Frankreich, König -- 1754-1793; France -- Kings and rulers -- Biography.; France -- History -- Louis XVI, 1774-1793.; France -- History -- Revolution, 1789-1799.; Kings, queens, rulers, etc.; France -- Histoire -- 1774-1793 (Louis XVI); BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Europe -- France.; Kings and rulers; France; BIOGRAPHY & AUTOBIOGRAPHY / Royalty; 1774-1799; Biography; Biographies; History; Biographies.